Greece : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Greece's integration into the euro area adds urgency to addressing the economic challenges. Securing stabilization gains within the Economic and Monetary Unit (EMU) will depend on labor cost developments, which need to restore an adequate level of competitiveness. Structural reforms, more equitable tax system, and public expenditure reform will be critical for securing stabilization gains. The high unemployment rate reduction will require comprehensive reforms targeted at the most affected labor market segments. An increasingly integrated and open market environment poses challenges for supervision and regulation.